An empirical analysis of the influence of human capital on enterprise innovation performance: A focus on the nature of enterprise ownership and enterprise scale - Lu, Meinong; Wu, Yongli (Nurture, 2023)
Purpose: This research examines how the heterogeneity of enterprise ownership nature and scale influences the relationship between human capital and innovation performance. Design/Methodology/Approach: This study makes use of data from the list of companies on China's expanding enterprise market from 2009-2020 through regression analysis using the panel data least squares approach. Findings: Higher levels of human capital and staff training have a positive impact on innovation performance but employee salaries and welfare levels have a negative impact on innovation performance. The effect of human capital stock and employee training on the performance of innovation in companies is more pronounced in state-owned enterprises or small companies. The nature of ownership or enterprise size has no significant effect on employee wage and welfare levels or the innovation performance of enterprises. Conclusion: The study's findings suggest that the relationship between human capital and innovation performance is complex and closely correlated with the type of ownership and size of the business. Research Limitations: More factors of firm heterogeneity such as firm age, industry and region were not verified. Practical Implications: It provides a new way for enterprises to improve innovation performance. Contribution to Literature: The purpose of this paper is to broaden the research viewpoint on how human capital investments affect the performance of enterprise innovation from two perspectives: the nature of enterprise ownership and the size of the enterprise.